2021
DOI: 10.1111/add.15598
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in substance‐induced psychosis: a register‐based national cohort study

Abstract: Aims We aimed to analyze whether people with substance‐induced psychosis (SIP), both those who convert and do not convert to schizophrenia, have higher all‐cause and cause‐specific mortality when compared to the general population. Design Prospective cohort study. Setting Nationwide Danish registers. Participants/Cases We included all people born in Denmark, living in Denmark on their 15th birthday, and age 15 or more during the study period from January 1, 1994, and August 10, 2017. Measurements Exposure was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Previous research has showed that comorbid personality disorder and substance use disorders are more common in those with psychotic depression than in people with non-psychotic depression, 7 , 20 and that personality disorder and substance use disorders are associated with psychosis and with increased mortality. 22 24 Our findings showed that these conditions did not explain the excess mortality in those with psychotic depression compared with severe non-psychotic depression. In other words, although these psychiatric comorbidities may add to the total burden of psychiatric morbidity, other factors are more important in determining the excess risk of mortality in psychotic depression.…”
Section: Discussionmentioning
confidence: 58%
“…Previous research has showed that comorbid personality disorder and substance use disorders are more common in those with psychotic depression than in people with non-psychotic depression, 7 , 20 and that personality disorder and substance use disorders are associated with psychosis and with increased mortality. 22 24 Our findings showed that these conditions did not explain the excess mortality in those with psychotic depression compared with severe non-psychotic depression. In other words, although these psychiatric comorbidities may add to the total burden of psychiatric morbidity, other factors are more important in determining the excess risk of mortality in psychotic depression.…”
Section: Discussionmentioning
confidence: 58%
“…Patients with schizophrenia exhibit a reduced life expectancy compared with the general population of about 15 years (Hjorthøj et al, 2017). Although diverse psychopathological conditions, such as increased substance abuse (Hjorthøj et al, 2021), unhealthy lifestyles (Jakobsen et al, 2018), or suicide risk might confound those results, the main reasons for the increased morbidity and early mortality are medical-conditions such as cardiovascular diseases or type 2 diabetes mellitus (T2DM) (Chan et al, 2021). Current literature suggests that the risk of previous medical conditions is increased by gestational problems (Hales and Barker, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 600 incident cases of any type of treated substance‐induced psychosis occur on a yearly basis in Denmark, and during recent years an increasing trend has been observed for cannabis‐induced psychosis [2]. Although the body of evidence regarding substance‐induced psychosis is limited, individuals with substance‐induced psychosis are found to have elevated risks of all‐cause and cause‐specific mortality, including suicide [3].…”
Section: Introductionmentioning
confidence: 99%